2004
DOI: 10.1158/0008-5472.can-03-3235
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ADAM9 in Non-Small Cell Lung Cancer Correlates with Brain Metastasis

Abstract: The "a disintegrin and metalloprotease" (ADAM) family contributes to regulation of the cell-cell and cell-matrix interactions that are critical determinants of malignancy. To determine the relationship between metastasis and ADAM proteins, we compared the mRNA levels of ADAM9, -10, -12, -15, and -17 in sublines of an EBC-1 lung cancer cell line that were highly metastatic to either brain or bone. ADAM9 mRNA levels were significantly higher in highly brain-metastatic sublines than in the parent or highly bone-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 36 publications
4
92
1
1
Order By: Relevance
“…of ADAM9 in non-small cell lung cancer has been correlated with brain metastases (24); furthermore, ADAM9 expression in pancreatic cancer has been suggested to be a prognostic factor in ductal adenocarcinoma (51). However, our studies, for the first time, point to the stromal component of an invasive tumor as the source of ADAM9 expression and thus suggest a functional role for stroma-derived ADAM9 in the context of local invasion of metastatic cancer cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…of ADAM9 in non-small cell lung cancer has been correlated with brain metastases (24); furthermore, ADAM9 expression in pancreatic cancer has been suggested to be a prognostic factor in ductal adenocarcinoma (51). However, our studies, for the first time, point to the stromal component of an invasive tumor as the source of ADAM9 expression and thus suggest a functional role for stroma-derived ADAM9 in the context of local invasion of metastatic cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…However, it was recently reported that in breast carcinoma increased expression of ADAM9 correlates with cancer progression (22) and elevated mRNA levels of both ADAM9 and ADAM12 have been found in liver metastases from colon carcinomas (23). Moreover, overexpression of ADAM9 in nonsmall cell lung cancer correlates with metastasis to the brain (24).…”
Section: Introductionmentioning
confidence: 99%
“…ADAM9 expression was increased in nonsmall cell lung cancer and correlated with brain metastasis, and the administration of anti-ADAM9 inhibited gastric cancer cell growth. 35,36 Overexpression of PPT1 protects cells against apoptosis mediated by the ras-akt (protein kinase B) caspase pathway in neuroblastoma cells, whereas anti-sense PPT1 increases cell death. 37,38 The ectopic expression of GRN promotes cancer cells invasiveness and forms large tumors in nude mice, whereas GRN expression depletion diminishes tumor growth and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…As induction of ADAM-8 production increases the invasive phenotype of cancer cells, this molecule might play a role in promoting disease dissemination. ADAM-9 mRNA and protein expression levels are enhanced in EBC-1 lung cancer cell line displaying a tropism for brain metastasis as compared to parent EBC-1 or EBC-1 cell line with a tropism for bone tissue [110]. Overexpression of ADAM-9 in EBC-1 and A549 lung cancer cells results in an increase of NGF-induced invasion and a higher adhesion of cells to brain tissue.…”
Section: Lung Cancermentioning
confidence: 92%